Attitudes towards mental health problems scale : Confirmatory factor analysis and validation in the Portuguese population - Cabral, Joana Moura (2016)
Several studies about stigmatization and shame toward mental health problems have contributed to minimizing the impact of these negative attitudes on people diagnosed with mental illnesses, on their families and on their communities. The Attitudes Towards Mental Health Problems Scale (ATMHP) is a self-report scale aimed at the assessment of attitudes toward mental health that involve several factors relating to attitudes and shame (internal, external, and reflected shame) when facing mental health problems. The goal of the current study was to translate, and to adapt this scale to the Portuguese population, and to study its psychometric properties in a sample of Azorean adults with and without psychiatric problems. The scale was administered to 411 participants with ages between 19 and 81 years. Confirmatory factor analysis was carried out on the initial model proposed by the authors of the ATMHP, and results showed a poor adjustment. An alternative model comprising an additional factor was tested and presented good model fit indices. Based on the alternative model, further analysis revealed that the scale has good psychometric properties.